If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -24 = 36 Reorder the terms: -24 + 12x = 36 Solving -24 + 12x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 12x = 36 + 24 Combine like terms: -24 + 24 = 0 0 + 12x = 36 + 24 12x = 36 + 24 Combine like terms: 36 + 24 = 60 12x = 60 Divide each side by '12'. x = 5 Simplifying x = 5
| y-3*2=0 | | y-5*-1=0 | | 3x+5=2x+50 | | y-5*2=0 | | 252/288= | | x^2+3x-5=180 | | 2*0=-y+4 | | 2*-2=-y+4 | | 3*-1=-y+4 | | 3*0=-y+4 | | 3*-1=y+4 | | 3*0=-y+2 | | 3*1=-y+2 | | 3*-2=-y+2 | | 2*1=-y+3 | | 2*-2=-y+3 | | k(x)=log(x) | | 5x+40=2x | | y=-0.9*50+118 | | y=-0.9*40+118 | | 12x^4-28x^3-9x^2+28x+12=0 | | y=-0.9*30+118 | | y=-0.9*20+118 | | 4x-1=631 | | 4x+34-35=976 | | x(34+x)+(-35+2x)=631 | | 2*5+5y=80 | | x(34+x)=(-35+2x) | | 2*10+5y=80 | | x(34+x)=(-35+2xX) | | x(34+x)=(-35+2*x) | | 36=7x+8 |